PERHITUNGAN DAN ANALISIS KESEIMBANGAN BEBAN PADA SISTEM DISTRIBUSI 20 KV TERHADAP RUGI-RUGI DAYA (STUDI KASUS PADA PT. PLN UPJ SLAWI) - Sukmadi, Tejo; Winardi, Bambang (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
Power distribution network is the part of electrical power system close to the customer or load side than the transmission network. To be better the electrical power system giving the electrical power supply to the customer, load balance must be achieved in each load points. Keseimbangan beban dapat tercapai jika tegangan yang dihasilkan dapat mensuplai beban secara penuh dari masing-masing titik beban maka sistem juga menjadi lebih baik dalam pemenuhan kebutuhan listrik. The load balance is important issue to decrease the voltage drop or power losses that can be occured in distribution line, so the information about load characteristics in each phases (R, S, and T) in some network area must be observed certain time. Keywords: distribution system, load balance, drop voltage, power loss.